The way of the kami or a descent into hell: Shinto in J-Horror through the films Noroi and Shikoku - Cardona García, Marta María (Estudios Complutenses de Asia Oriental, 2025)
The term J-Horror was born in the late 90s to refer to Japanese horror films. It soon became not only one of the most prolific and exported subgenres of Japanese cinema, but also a mass phenomenon, which promoted the creation of numerous remakes in the West. With a marked aesthetic and appealing to psychological horror and B-movies, J-Horror resorts to a wide range of resources to capture the fears, conflicts and tensions that exist at a social and political level in Japan. On this occasion we will investigate the importance of religious elements, and specifically Shintoism, through the cult films Noroi and Shikoku. This analysis of a symbolism that can be obscured for culture reasons will allow us to delve into the significance of the selected films and their social and cultural impact.